If (a − b), (b − c), (c − a) are in G.P.,


If ( b), (b − c), (c − a) are in G.P., then prove that (a + b + c)2 = 3 (ab + bc + ca)


$(a-b),(b-c)$ and $(c-a)$ are in G.P.


$\Rightarrow b^{2}-2 b c+c^{2}=a c-b c+a b-a^{2}$

$\Rightarrow a^{2}+b^{2}+c^{2}=a b+b c+c a$$\quad \ldots \ldots$ (i)

Now, LHS $=(a+b+c)^{2}=a^{2}+b^{2}+c^{2}+2 a b+2 b c+2 c a$

$=a b+b c+c a+2 a b+2 b c+2 c a \quad[$ Using (i) $]$

$=3 a b+3 b c+3 c a$

$=3(a b+b c+c a)$


Leave a comment


Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now